Social constructionism and theology - Hermans, C. A. M. (Christiaan Andreas Maria), 1955- (Empirical studies in theology, 2002)
Although its forms vary, social constructionism is one to which not only social scientists, but also researchers in the psychology and sociology of religion, adhere. This volume demonstrates the importance of reflection on the emerging concept of social constructionism in the social sciences.